2010
DOI: 10.1111/j.1742-481x.2010.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

The experience of children and families with lymphoedema – a journey within a journey

Abstract: This paper reports on a study in the UK that explored the experience of children suffering with Lymphoedema and that of their families. Qualitative data was collected from 20 children between the ages of 6 and 18 and their respective parents. Single, semi-structured interviews were used in which children and their parents were asked to share how lymphoedema impacted on their family life. Children were asked about their school experience, their dreams and their aspirations. Three categories emerged. Firstly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Articles excluded from this review included recent research about management of pediatric lymphoedema, which has concentrated on the development of an appropriate response to children within an adult service [18], and the psychosocial support needed by the families of children with lymphoedema [4,5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles excluded from this review included recent research about management of pediatric lymphoedema, which has concentrated on the development of an appropriate response to children within an adult service [18], and the psychosocial support needed by the families of children with lymphoedema [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…Although children with lymphoedema are estimated to be few in number, the impact on their lives and that of their families is large as parents struggle to manage the psychological and financial impact of lymphoedema and worry about the long term implications for their child [4,5]. Diagnosis of lymphoedema is of-ten delayed: a review of services for people of any age having lymphoedema in Victoria, Australia found that it took an average of 9.4 years for those with primary lymphoedema to be diagnosed, in contrast to an average of 1.5 years for those with secondary lymphoedema [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to genuinely engage in meaningful nursing care for children requires practitioners to have an insightful appreciation of what it means to be ill, and how being ill or living with a disability can intrude upon taken‐for‐granted aspects of a child's daily life (Guell, 2007; Moffatt & Murray, 2010; Protudjer, Kozyrskyj, Becker, & Marchessault, 2009). Qualitative research provides a platform for a more informed and illuminative understanding of how illness can shape a child's life‐world, which in turn can help children's nurses to provide empathic nursing care (Carter, Marshall, & Sanders, 2009).…”
mentioning
confidence: 99%
“…They felt safe in taking breaks from their garments because they believed they knew their body and could manage increased swelling. However, adolescents feel that their non-adherence is misinterpreted as laziness, rather than a method of coping 18. Concerns about pain and discomfort, or their condition worsening kept them motivated to regularly complete components of their treatment that they could do in private.…”
Section: Discussionmentioning
confidence: 99%